How daily positive affect increases students' mental health, in mandatory quarantine, through daily engagement: The moderating role of self-leadership - Junça Silva, A.; Silva, D.; Caetano, A. (Heliyon, 2022)
The COVID-19 crisis has had significant impacts on mental health. Students are dealing with an uncertain context, not only due to COVID-19 but also because most of them have never been involved with the challenges of online school. The COVID-19 situation presents daily challenges that require students to respond adaptively. However, little is known about how students handle their daily emotions, in such challenging settings. Drawing on the broaden-and-built theory, we developed a multilevel model arguing that daily-positive affect would enhance daily engagement, and this would be positively related to students' end-of-the-day mental health. We also predict that the mediating path would be stronger for students with higher levels of self-leadership. To achieve the goals, we conducted a 5-day diary study (n = 64*5 = 320). Results from multilevel modeling showed that positive emotions trigger academic engagement which, in turn, increases mental health, both at the within and between-person level. Results also demonstrated that self-leadership strengthened the positive mediating path, for students with higher levels of self-leadership. Positive affect appears to be a significant predictor of mental health in higher education settings. Moreover, developing self-leadership is an added value, that may be conceived as a personal resource, and may protect students from the uncertainty triggered by the COVID-19 crisis.